Observations at a Yellow-eared Toucanet (Selenidera spectabilis) nest - Rodríguez, Alan (2018)
What little we know of the breeding biology of Selenidera toucanets comes from only two of the eight species. For most species the breeding season is approximated through indirect evidence (e.g., gonad size in collected specimens and juvenile observation), but few nests have been found. Here, we describe nest architecture, parental care behavior, and chick characteristics of the Yellow‐eared Toucanet (S. spectabilis) based on a single nest found in Costa Rican mid‐elevation forest. The nest was inside a natural cavity of a live tree, contrary to the previous report of an old woodpecker nest in a snag. Both parents provide insects and fruits to the chicks inside the nest. The chicks hatch with closed eyes, pale pink skin, and a bicolor beak.